Pengaruh Penambahan Buah Asam (Tamarindus indica L.) Terhadap Karakteristik Loloh Don Teter (Solanum erianthum) - Ryantama Swastika Braja, I Wayan; Mayun Permana, I Dewa Gede; Suter, I Ketut (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPADO - 10.24843/itepa.2021.v10.i01.p10, 2021)
Loloh teter leaf is one of the traditional drinks in Bali, it made from raw material of teter leaf and other matter such as tamarind fruit, sugar and salt. The study aims to determine the effect of additional tamarind fruit ( Tamarindus indica L. ) to produce Loloh Teter leaf ( Solanum erianthum ) with the best characteristics. The experimental design used was a Completely Randomized Design (CRD) with the addition of tamarind fruit treatment consisting of 6 levels, namely : 0%, 0.5%, 1%, 1.5%, 2% and 2.5%. The treatment was repaeated 3 times for abtaining obtained 18 experimental units. The data obtained were analyzed by variance and if the treatment had significant effect followed by Duncan Multiple Range Test (DMRT). The results of this study indicate that the treatment of tamarind fruit addition has a very significant effect (P<0,01) on total phenolics, total flavonoids, vitamin C, antioxidant activity, total solids, color (hedonic test) and taste (scoring test). The best treatment in this study was the addition of 2,5% tamarind fruit with the total phenolics 0.86 GAE/100ml, total flavonoids 0.48 QE/100ml, vitamin C 26.39 mg/100ml, antioxidant activity 47.05% with IC 50 valued 271,382.73 ppm, total solids 7.44%, the color is usual as well as, the aroma is rather liked, the teste is sour and rather liked and overall acceptance is rather liked.